Halal Certification The Role of Socialization Communication in Shaping Perceptions and Intentions of MSMEs to Apply for Halal Certification: The Role of Socialization Communication in Shaping Perceptions and Intentions of MSMEs to Apply for Halal Certification - Dhani Salman; Bisma Widyawan; Joni Haryanto (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2026)
Halal certification is an important instrument for improving the competitiveness, consumer trust, and regulatory compliance of Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze MSME actors’ perceptions of food safety outreach communication and their intentions to apply for halal certification in Depok City. A descriptive quantitative approach supported by qualitative analysis was employed. Data were collected through questionnaires from 23 participants of the MSME Food Safety Outreach using a total sampling technique and analyzed using descriptive statistics and thematic analysis. The findings indicate that most respondents perceived the outreach as easy to understand, increased their knowledge of halal certification, and recognized its importance for their businesses. The majority also expressed interest and intention to apply for halal certification. The study concludes that effective outreach communication contributes to positive perceptions, trust in facilitators, and stronger intentions to pursue halal certification among MSME actors